The Impact of Training, Culture, and Leadership on Electronic Performance - Tobari Tobari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the impact of training, organizational culture, and managerial capability on E-Performance, as well as the subsequent influence of E-Performance on employee performance within the City Government. The research is intended to offer valuable insights for academics and practitioners focused on promoting digital transformation and improving performance in the public sector. Additionally, it enriches the theoretical discussion by incorporating essential organizational behavior concepts into the context of digital governance. Performance and its implications for Employee Performance within the City Government. Using a quantitative approach, data were collected from 413 employees through structured questionnaires and analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). While Training directly improves E-Performance, it does not have a significant direct impact on Employee Performance. This research contributes to the understanding of digital transformation in the public sector, particularly in Indonesia, by highlighting the critical roles of organizational culture and managerial capabilities in facilitating this transformation. The study underscores the importance of fostering a supportive culture and enhancing managerial skills to maximize the benefits of digital technologies in improving employee productivity. The findings reveal that both Managerial Capability and Organizational Culture significantly enhance E-Performance, which in turn positively affects Employee Performance